Rejection of emerging organic contaminants by nanofiltration and reverse osmosis membranes : effects of fouling, modelling and water reuse : dissertation submitted in fulfilment of the requirements of the Board for Doctorates of Delft University of Technology and of the Academic Board of the UNESCO-IHE Institute for Water Education for the Degree of DOCTOR to be defended in public on Tuesday, 9 February 2010, at 12:30 hours in Delft, the Netherlands /: effects of fouling, modelling and water reuse : dissertation submitted in fulfilment of the requirements of the Board for Doctorates of Delft University of Technology and of the Academic Board of the UNESCO-IHE Institute for Water Education for the Degree of DOCTOR to be defended in public on Tuesday, 9 February 2010, at 12:30 hours in Delft, the Netherlands. (2010) - Yangali Quintanilla, Victor Augusto
No abstract available